Exploring Factors Influencing Students’ Entrepreneurial Intention in Vocational Colleges Based on Structural Equation Modeling: Evidence From China - Fu, Xiaoqian; Yan, Tianming; Tian, Yumi; Niu, Xinchen; Xu, Xin; Wei, Yao; Hu, Qifan; Ouyang, Zhongming; Wu, Xueshi (Frontiers in Psychology, 2022)
With the proposal of “mass entrepreneurship, mass innovation” and other ideas, the demand for entrepreneurial talent in China is increasing, but the supply of entrepreneurial talent is far insufficient. Consistent with theory of social cognition and planned behavior, this study outlines a conceptual model including entrepreneurial intention (EI), emotional competency (EC), entrepreneurial self-efficacy (ESE), entrepreneurial attitude (EA), entrepreneurial education (EE), and subjective norms (SN). A structural equation model was applied through a questionnaire survey of 382 vocational college students in Jiangxi province to test the relationship between the constructs in the model. The results show that, firstly, EA, EE, ESE, and EC have positive effects on EI, while the positive effect of SN on EI is not supported. Secondly, a mediating role is played by ESE and EA in the association between EI and EE. Thirdly, ESE and EA play mediating roles in the relationship between EI and EC. Some implications of EI for schools and students were discussed.